Questions of authenticity in the Bo-Kaap tourism experience. - Göpper, Janine (My University, 2014)
This research report will attempt to show that, in an attempt to cater for tourist tastes for the exotic, a Cape Malay identity has been constructed for the residents of the Bo- Kaap community which is made to date back to the 17th Century. Two books from popular tourist literature and three travel guides have been analysed. Furthermore, this research report will demonstrate how the built environment of the city and its surrounding areas can provide us with a much more nuanced narrative than the one which is currently being presented to tourists.
Keywords: Tourism--South Africa--Bo-Kaap (Cape Town).